Physical and Chemical Properties of Biscuits Fortified with Bee Pollen - Anis, Ulfah; Yuwana , Yuwana; Intara , Yazid Ismi; Gusriani, ⁠Ika (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Functional foods, such as bee pollen, contain nutrients and positively affect health. Bee pollen is a natural bee product with high antioxidant potential. Phenolic compounds are found in bee pollen as antioxidants. Other contents of bee pollen are protein, minerals, and ash. Bee pollen contains several essential amino acids required by the human body. Bee pollen has been used to fortify various food products, such as yoghurt, bread, and biscuits. The study aimed to evaluate bee pollen biscuits. The experimental design was a Completely Randomized Design (CRD) with one factor. The factor was substituted for bee pollen (0%, 5%, 10%, 15%, 20%) for wheat flour. The research revealed that the substitution of bee pollen had a significant impact on the total phenolic content, CIE Lab values (Lightness, a*, b*), hue angle, and chroma of the biscuits. In contrast, substituted bee pollen did not affect the protein and ash content. The results showed that bee pollen has a positive effect on the quality of the biscuit, indicating its potential as a functional food.